VD_FINDINFO Décision / 2015 / 811 vom 28. Oktober 2015 - VD Tribunal cantonal (2015)
CLASSEMENT DE LA PROCÉDURE, QUALITÉ POUR RECOURIR, LÉSÉ, LÉSION CORPORELLE | 117 CPP (CH), 319 al. 1 CPP (CH), 382 al. 1 CPP (CH)